Evaluating The Private Banking Sector Performance Depending On CAMELS: Applied Study On Private Banks Listed In Damascus Stock Market - صندوق, عفيف; المشعل, ياسر; حسن, علي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aimed to assess the performance of the private banking sector in Syrian Arab Republic during the period between 2010-2018 from a supervisory prospect of the Central Bank to determine the strengths and weaknesses of the banking sector in Syrian Arab Republic. We gathered the statistical data issued by local banks (14 traditional and Islamic banks). The performance of the banks was evaluated separately using the CAMELS model, where the study showed average performance of the operating banks. The researchers deliberately used indicators of capital adequacy, asset quality, management efficiency, profitability, liquidity, and sensitivity to market risks. In addition, the researchers tried to study the effect of stock market risk on the performance of the banking sector by forming a portfolio of shares of banks operating in Syria. The results of the statistical analysis using the SPSS program, through the Discriminant Analysis test, showed the presence of an impact of a number of indicators on the performance of the banking sector. In the end, a model for evaluating the performance of the banking sector was obtained using a multiple regression model and the model is able to explain the performance of the banking sector by 88.4%.